The Collaboration of Statistical Process Control and Root Cause Analysis Method in Maintaining The Quality of Biometric Solution Products - Taufiq Agus Supriyanto; Slamet Riyadi; Fausta Ari Barata (Management Dynamics: International Journal of Management and Digital Sciences, 2025)
The quality of biometric solution products needs special attention. This is based on complaints submitted by consumers. Following up on these complaints, research needs to be conducted to find out how consumers feel about biometric solution products, find the root of the problem that affects product quality, and also find solutions that can be done to maintain the quality of this biometric solution product. This study uses a qualitative research method with a case study approach at a biometric solution provider company. The research sample is a biometric solution product produced from July 2023 to March 2025. The collaborative application of the Statistical Process Control and Root Cause Analysis methods is used to determine whether product damage is still within control limits and also to determine the main causes of the decline in product quality. The results of the study showed that the reported product damage reached 23.6%, which exceeds the maximum product damage standard determined by management, which is 10%. Although the product damage exceeds the maximum standard, the results of calculations using the control chart show that the damage is still within normal control limits. However, several factors causing product quality problems are determined by human factors, materials, methods and measurements. The lack of technical capabilities and technical documentation from the Research and Development team shows a major influence on the problems that occur. Improvement steps can be taken through improving Research and Development procedures, completeness of technical documentation, and increasing the technical capabilities of the Research and Development team.